Risk factors in the development of gastric adenocarcinoma in the general population: A cross-sectional study of the Wuwei Cohort - Chen, Zhaofeng; Zheng, Ya; Fan, Ping; Li, Min; Liu, Wei; Yuan, Hao; Liu, Xin; Zhang, Zhiyi; Wu, Zhengqi; Wang, Yuping; Ji, Rui; Guo, Qinghong; et al. (Frontiers in Microbiology, 2023)
Several risk factors have been identified for the development of gastric adenocarcinoma (GAC), where the control group was usually a healthy population. However, it is unclear at what stage known risk factor exert their inﬂuence toward the progression to cancer. Based on the Wuwei Cohort, we enrolled 1,739 patients with chronic non-atrophic gastritis (no-CAG), 3,409 patients with chronic atrophic gastritis (CAG), 1,757 patients with intestinal metaplasia (IM), 2,239 patients with low-grade dysplasia (LGD), and 208 patients with high-grade dysplasia (HGD) or GAC to assess the risk factors between each two consecutive stages from no-CAG to GAC/LGD using adjusted logistic regression. We found that different groups of risk factors were associated with different stages. Age, occupation of farmer, low annual family income, helicobacter pylori (H. pylori) infection, drinking, eating hot food, histories of gastritis and peptic ulcer were associated with the development of CAG. Age, illiteracy, H. pylori infection, smoking, eating hot food, eating quickly, and histories of gastritis and gallbladder diseases were associated with the progression to IM from CAG. Male, occupation of farmer and history of peptic ulcer were associated with the development of LGD from IM. Age, male and polyp history appeared to be risk factors associated with the development of GAC/HGD from LGD. In conclusion, it seems that most risk factors function more as a set of switches that initiated the GAC carcinogenesis. H. Pylori eradication and control of other risk factors should be conducted before IM to decrease the incidence of GAC.